Inclusive banking, financial regulation and bank performance: Cross-country evidence - Ahamed, M. Mostak; Ho, Shirley J.; Mallick, Sushanta K.; Matousek, Roman (Journal of Banking & Finance, 2021)
This paper investigates whether inclusive banking can boost bank-level performance, using an international sample of 1,740 banks over the period 2004-2015. We find that there is a significant positive association between financial inclusion and bank efficiency. Greater financial inclusion helps banks in reducing the volatility of their deposit-funding share as it provides more stable long-term funds for banks, while also mitigating the adverse effects of their return volatility. The association is stronger in countries with limited restrictions on banking activities or more capital regulation stringency as the deposit channel enables greater flow of low-cost funds for high-return investments. The results are robust to instrumental variable analysis, multiple dimensions of financial inclusion (supply, demand, and pro-access policy), and a difference-in-differences estimator that exploits cross-country and temporal variations in actively promoting an inclusive agenda, further confirming that inclusive financial development can be beneficial for banks.